1987
DOI: 10.1111/j.1600-0447.1987.tb02906.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of dementia: A quantitative integration of the literature

Abstract: Data from studies of dementia prevalence between 1945 to 1985 were analyzed statistically. Prevalence rates were found to vary as a function of methodological differences between studies. However, despite these differences, the relationship between prevalence and age was found to be consistent across studies, with rates doubling every 5.1 years. Across studies, Alzheimer's disease (AD) was found to be more common in women, with a tendency for multi-infarct dementia (MID) to be more common in men. There were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
557
4
74

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,189 publications
(668 citation statements)
references
References 32 publications
33
557
4
74
Order By: Relevance
“…LH increases may be responsible for cognitive decline and vulnerability to AD in women previously attributed to loss of E. Post-menopause E loss has been associated with cognitive decline (Birge et al, 2001;Genazzani et al, 1992) and the susceptibility of women to AD, as women have AD 2:1 compared to men (Breitner et al, 1988;Brookmeyer et al, 1998;Jorm et al, 1987;McGonigal et al, 1993;Rocca et al, 1991). However, increases in LH following menopause may be influential as women experience a 3-to 4-fold increase in the concentration of serum LH following menopause (Chakravarti et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…LH increases may be responsible for cognitive decline and vulnerability to AD in women previously attributed to loss of E. Post-menopause E loss has been associated with cognitive decline (Birge et al, 2001;Genazzani et al, 1992) and the susceptibility of women to AD, as women have AD 2:1 compared to men (Breitner et al, 1988;Brookmeyer et al, 1998;Jorm et al, 1987;McGonigal et al, 1993;Rocca et al, 1991). However, increases in LH following menopause may be influential as women experience a 3-to 4-fold increase in the concentration of serum LH following menopause (Chakravarti et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In a meta-analysis assessing 27 studies, Jorm et al 6 have reported that the prevalence of dementia doubles every 5.1 years from the age of 60 years. In the sample studied, patients with chronic kidney disease undergoing a HD program showed, regardless of gender and duration of the dialysis treatment, a cognitive impairment above that expected for their respective age bracket (26%, 47%, and 71%).…”
Section: Discussionmentioning
confidence: 99%
“…Uma revisão de estudos de prevalência mostra taxas médias que variaram de 0,7%, na faixa etária de 60-64 anos, a 38,6%, na faixa de 90-95 anos 4 . No Brasil, existem poucos estudos de prevalência de demência.…”
Section: Introductionunclassified